VOSMIL: DIGITAL WEBSITE APPLICATION PLATFORM INNOVATION AS A MEDIA FOR RECORDING OF UMKM KONCONE NGEMIL FINANCIAL REPORTS - Labbaika Dwi Ayu Rahmawati; Elsa Pudyaningrat (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Financial reports are one of the important factors in running every business. Financial reports can be used as a reference for determining future economic goals. As is the case with the Koncone Ngemil UMKM business sector where financial reports are very well cared for, but their financial records use the manual method, namely by using large and striped notebooks. The use of notebooks as a means of recording financial reports is prone to damage, inaccuracy, and recording errors that can affect the validity of existing financial reports. So that innovation is needed in the form of a digital website application that can be used as a medium for recording their financial reports, the application is VOSMIL. This study aims to determine the effectiveness of using the VOSMIL digital website application for UMKM Koncone Ngemil in recording financial reports. The research method used is a descriptive method, which describes, describes, and compares data. The data collection technique is qualitative through secondary and primary data. After the data is collected, it is then analyzed using SWOT. The results of this study indicate that the use of the VOSMIL digital website application can provide benefits and is effective in recording financial reports for UMKM Koncone Ngemil. Keywords: Financial Reports, Accounting, UMKM, Digital Website Applications